READERS' POSmONING IN RECHARD MANN'S PLOTS AND SCBEMES THAT BROUGHT DOWN SOEHARTO (PSBDS): A STUDY ON INTERPERSONAL MEANlINGS - Sugeng Purwanto (Soegijapranata Catholic University, 2008)
The real cause of Soeharto's fall from the Indonesian presidency remains a mystery. Richard Mann (1998) launched three significant rhetorical questions, i.e. (1) Was President Soeharto toppled by student demonstrators and people power? (2) Was he brought down by the withdrawal of supportfrom the United States? (3) Or, was his suddenfall brought about by all of the two plus large doses of OrIental plotting and scheming? This article tries to investigate the readers'positioninginMann's Plots and Schemes that Brought Down Soeharto (pSBDS) with a view to describing the Appraisal system used in the textbook to achieve the desired interpersonal meanings, employing the analytical framework of Appraisal Theory (Martin and Rose 2003,' White 1998), an extended mode of Hallidays Functional Grammar (1994) and Systemic Functional Linguistics (Eggins 1994). The study yields some rhetorical strategies (Strayers 2004) with which to align the readers As well, the study pedagogically implies that readers should be aware of the writer's strategies as to what direction the readers are positioned in text, resulting in the importance of critical reading and cross-referencing in order to folly understand a text.